Peningkatan Kapasitas Pelaku Usaha Perikanan di Desa Pela Kabupaten Kutai Kartanegara Melalui Penyuluhan Manajemen Strategi Pemasaran - Fitriyana Fitriyana; Helminuddin Helminuddin; Said Abdusysyahid; Irman Irawan; Wahyu Fahrizal; Yulianti Yulianti; Dwi Larasati; Sudewi Sudewi; Baiq Sulistiyorini; Rudi Yakob (Jurnal Kabar Masyarakat, 2024)
Marketing of fishery business products is technically a little different from non-fisheries, this is because the marketing flow time from producer to consumer must be shorter, this is done in order to maintain freshness and optimal protein content in the fish. Therefore, efforts are needed to provide technical guidance for business marketing management. Lack of knowledge of the importance of groups is an obstacle in providing assistance to fishermen. so it is necessary to provide ongoing assistance by related agencies and academics to change the mindset and fate of fishermen towards a better standard of living. Extension activities were carried out on Saturday, May 11 2024 in Pela Village, Kota Bangun District, Kutai Kartanegara Regency. The approach method used is mapping potential locations, counseling, training and assistance with business marketing management. The result of community service is that fishing communities can understand the importance of joining or forming groups to achieve the same goals, and fishermen understand the importance of marketing management in an effort to increase income and economic welfare.